PENGEMBANGAN KAWASAN PERMUKIMAN SUBURBAN BERBASIS TRANSIT ORIENTED DEVELOPMENT (TOD): Studi Kasus: Kawasan Stasiun Pasar Nguter, Sukoharjo, Jawa Tengah - Christian Nindyaputra Octarino (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2016)
Title: The Development of Suburb Residential Area Based on Transit Oriented Development (TOD) The rapid growth and development of the city has impacted on the increasing of city population and traffic density which lead to various urban problems. The development of suburbs as a satellite city is considered as an appropriate solution to reduce the main city‘s load. This area could be developed into residential uses to provide living area for commuters. The railway that connects Solo and Wonogiri is considered as a major potential to create the integration between Solo as the main city and other areas as regional supports. Pasar Nguter Station is located on the route of Solo-Wonogiri railway and has great potential. The aim of this research is to examine and explore possibilities of Pasar Nguter Station to be developed as residential area based on Transit Oriented Development (TOD). This research will assess the existing condition surrounds Pasar Nguter Station based on the principal aspects of TOD such as mobility, land use, intermodal network, etc. to analyze the gap between existing and ideal conditions to formulate the most appropriate regional development strategy.